Financial Ratio Analysis: A Case Study from Milan Fashions Coat Company - Richter , Ronald; Guarino , Arthur S. (An Overview on Business, Management and Economics Research Vol. 5, 2023)
Financial measurements have traditionally served as the cornerstone for measuring company performance. This case study examines the debt status of a company as it strives to expand its manufacturing operations. The company requires financial money to expand, but its business venture and financial status are regarded risky, therefore it must contact a commercial bank to obtain funds. A bank lending officer must review the company's financial statements to determine whether a loan is feasible. The lending officer must evaluate significant portions of the firm's financial accounts, do ratio analysis, and then decide whether to extend the loan.